Pengaruh Inflasi, Profitabilitas dan Ukuran Perusahaan Pada Return Saham Perusahaan Terindeks LQ45 - Dewi, Ida Ayu Laksmi; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2019)
Capital markets are places that combine those who lack funds with those who excess funds or called investors. Investors can invest in LQ45 indexed companies that have high market capitalization and liquidity. The purpose of this study is to examine the effect of inflation, profitability and firm size on stock returns. The study population was all LQ45 indexed companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2017. The samples were determined by purposive sampling technique. The sample criteria are listed in the LQ45 index from 2015 to 2017 so that there are 34 samples obtained with 102 observations. The analysis technique is multiple linear regression analysis. The results of the analysis show that inflation has a negative effect on stock returns, profitability and the size of the company has no effect on the return of LQ45 index companies. Keyword:  Inflation, profitability, company size, stock return